Multi-national perceptions on challenges, opportunities, and support structures for dual career migrations in European student-athletes - Fuchs, P. X.; Doupona, M.; Varga, K.; Bon, M.; Cortis, C.; Fusco, A.; Castellani, L.; Niemisalo, N.; Hannola, H.; Giron, P.; Förster, J.; Capranica, L.; et al. (PLOS ONE, 2021)
Despite Dual Careers (sports and education) and mobility of students being priorities in the funding policies of the European Commission, migrating student-athletes report severe challenges and decreased performance or dropouts at sport and academic levels. The objective of this study was to depict and assess the perceptions on challenges, support services, and their effectiveness in consideration of specific characteristics of participants and migrations. Based on a meta-synthesis and previous findings, a 50-items questionnaire was developed and completed by 245 student-athletes in 5 European countries. Participants with Dual Careers migration experience (n = 140) were considered for analyses of qualitative and quantitative (ordinal 5pt-Likert-scaled and metric) data on the Dual Career status, migration characteristics, received services, and outcomes. Chi-square-tests were conducted for differences between countries and genders at a significance level of p < .05. Country-related differences were found for experiences and intentions to migrate (X2(12) = 50.52, p<0.001), duration of the migration (X2(16) = 38.20, p = 0.001), financial support (X2(8) = 29.87, p<0.001), and decreased performances in academics (X2(16) = 56.12, p<0.001) and sports (X2(16) = 31.79, p = 0.01). Gender-related difference emerged in financial support (X2(4) = 10.68, p = 0.03), duration of the migration (X2(4) = 14.56, p = 0.01), and decreased academic performance (X2(4) = 10.57, p = 0.03). Tutoring and counselling support was ranked as the most effective support, especially when received from the academic field (4.0±1.0 pt) and others (4.1±0.8 pt), followed by online services from sport and academic sectors (both: 3.9±0.9 pt). Considering the pervasive globalization of sport and education, Dual Career migration can contribute to the development of a European sport culture. The high ratio of migrating student-athletes underlines the relevance of migrations in the field of Dual Careers. This study contributes to the literature by adding insights on practices, challenges, supports, and outcomes perceived by student-athletes migrating in Europe. Moreover, country- and gender-related differences support the consideration of specific characteristics and reveal critical factors in specific target groups. The findings contribute to identifying requirements and effective support measures in Dual Career migrations and can be used to improve support services.